The Influence of Price and Promotion Through Instagram Social Media on Generation Y Tourists' Purchase Interest at Four Points By Sheraton Bali, Seminyak - Wibawa, Anak Agung Putu Sebastian Ardika; Pitanatri, Putu Diah Sastri; Wiartha, Nyoman Gede Mas (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
The purpose of the research is to test and determine the effect of price and promotion through Instagram social media partially and simultaneously on the purchasing interest of Generation Y tourists at Four Points by Sheraton Bali, Seminyak. The research conducted is a quantitative research with a population of Generation Y tourists who know Four Points by Sheraton Bali, Seminyak. The sample used was 100 respondents. In conducting data analysis, the techniques used were Multiple Linear Regression, t-test, f-test, and Determination Coefficient using SPSS. Based on the results of the study, it was found that the calculated f value> f table = 143.734> 3.09 and the significance value <α = 0.00 <0.05 and it can be concluded that price and promotion through Instagram social media have a positive and significant effect simultaneously on the purchasing interest of Generation Y tourists at Four Points by Sheraton Bali, Seminyak.